PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF TIPE KOSAJI PADA PEMBELAJARAN FISIKA - Rumansyah -; Kosim -; Harry Soeprianto (Postgraduate, University of Mataram, 2016)
This study aims to develop a cooperative learning model of KOSAJI type that valid, practical and effective. KOSAJI of cooperative learning model is a collaboration between cooperative learning model type STAD and Jigsaw in physics learning. The method used was the research development model adopted Dick and Carey with ten stages which includes a needs analysis to determine the objectives, formulate indicators, the analysis of the students and the context, the establishment of specific goals of learning, the development of assessment tools of learning, the development of learning strategies, the development and selection of material lesson, formative evaluation, revision of the device, and a summative evaluation of the effectiveness of the device. This research was conducted at SMAN 1 Mataram. KOSAJI cooperative learning model developed together with learning devices such as lesson plans, worksheets, questionnaires students' attitude towards physical and cognitive achievement test. KOSAJI learning model along with the device has been through expert validation, test a small group, limited field testing and large-scale (summative evaluation). Implementation KOSAJI learning model in teaching physics to minimize shortage and optimize the advantages that exist in both the type of cooperative learning model. Based on expert validator test KOSAJI learning model and is well worth learning device used with a percentage value of 94.99% . After going through the stages of the test group was small and limited field KOSAJI learning model can be applied to both in terms of the response of the students (80.52 % on a small test group and 83.41% in the limited field testing ), the response of teachers (76.92 % in the small test group and 82.69 % limited field tests) and enforceability of RPP (86.61 % on a small group of test and 86,62 % in limited field test) with some revisions .Summative test results showed that the learning model KOSAJI effectively improve students' cognitive learning outcomes with increased value in terms of pretest and posttest of 41.93%. Therefore, the development of cooperative learning in teaching physics KOSAJI proved valid, practical and effective.Keyword: KOSAJI Cooperative Learning Model, Physics Learning